Непрофесійний фагоцитоз клітин карциноми легені Льюїс за різних умов їх росту - Kolesnik, D.; Lykhova, O.; Stepanov, Y.; Solyanik, G. (PH Akademperiodyka, 2025)
Background. Phagocytosis occurs in almost all cell types of multicellular organisms. Based on their efficiency, cells are classified as professional or non-professional phagocytes, with cancer cells belonging to the latter. This property of cancer cells underlies the formation of “cell-in-cell” structures, the high frequency of which is often associated with invasion and metastasis of malignant tumors. Aim. To investigate the ability of Lewis lung carcinoma (LLC) cells to perform non-professional phagocytosis and to analyze how this process depends on cancer cell growth conditions. Materials and Methods. A low-metastatic variant of LLC cells (LLC/R9) was used. Phagocytic activity was examined under anchorage- dependent and anchorage-independent growth conditions, in both standard and glucose-free culture media, using fluorescent latex beads (1.0 μm in diameter). Results. LLC/R9 cells demonstrated phagocytic activity, which increased nearly fourfold under anchorage-independent conditions, irrespective of E-cadherin expression. Glucose deprivation reduced the percentage of bead-engulfing cells by more than twofold under both growth conditions, while increasing the number of beads internalized per cell. This indicates a pronounced heterogeneity within the cancer cell population in their sensitivity to phagocytic activation under glucose deficiency. Conclusions. Non-small cell lung cancer LLC/R9 cells are capable of phagocytosis, which is markedly enhanced under anchorage-independent growth and only weakly influenced by glucose deprivation.